Advanced diagnostic strategies for the detection and identification of seed-borne viruses at ICARDA to enhance seed health security - Kumari, Safaa; Moukahel, Abdulrahman (the Mediterranean Phytopathological Union, 2025)
ICARDA’s Seed Health Laboratory (ICARDA-SHL) is responsible for the monitoring, clearance, and documentation of the safe germplasm movement at the Center. The laboratory processes over 50,000 samples annually for seed-borne pathogens/pests, for the purpose of short- and long-term conservation and global distribution. This rigorous screening process is essential for preventing the spread of seed-borne pests across borders, especially viruses that can be transmitted further by insect vectors upon introduction. This has made the management of seed-borne viruses more challenging, as infected seeds can introduce the virus into new areas and lead to infections in subsequent growing seasons. Early detection and accurate diagnosis of viral diseases are critical for implementing effective control measures and strategies. In this context, ICARDA-SHL is actively engaged in the development, validation and dissemination of advanced diagnostic tools and protocols for germplasm health testing, facilitating technology transfer to NPPOs. Accordingly, ICARDA-SHL has developed and applied various molecular tests for the detection and identification of seed-borne legume viruses, including IC-RT-PCR, uniplex RT-PCR and multiplex RT-PCR in a single direct test. These advanced diagnostic techniques allow rapid analysis of large numbers of samples at a relatively low cost, high throughput, short execution times and enhanced accuracy, thus ensuring the availability of certified seeds, which are key strategies to mitigate the spread of seed-borne legume viruses that cannot be controlled by conventional plant treatments. In this presentation, validated molecular tools for the detection and identification of selected legume viruses (e.g. AMV, CMV, BYMV, PSbMV) applied by ICARDA-SHL will be described.